2013
DOI: 10.4238/2013.january.7.1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of earl millet cultivars using both microsatellites and enzymatic markers

Abstract: ABSTRACT. The increasing number of protected and registered cultivars and problems involving seed commercialization make distinction and identification of cultivars imperative. Millet (Pennisetum glaucum), a crop species with protected cultivars in Brazil, has been the target of seed piracy. Thus, with the objective of identifying different lots with regard to origin, we characterized six cultivars of commercialized millet of proven origin by means of the electrophoretic patterns of the isoenzymes alcohol dehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Therefore, the identification of seed varieties is an urgent problem to be solved in agricultural production, seed sales, and food processing. The common methods of seed identification in China and abroad include morphological methods, the gel electrophoresis of soluble seed proteins [4,5], direct analysis with real-time mass spectrometry [6], isoenzyme electrophoresis [7], liquid chromatography [8], and simple sequence repeat (SSR) analysis [9]. Morphological methods are highly demanding of experience for appraisers and the identification accuracy is easy subject to subjective factors.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the identification of seed varieties is an urgent problem to be solved in agricultural production, seed sales, and food processing. The common methods of seed identification in China and abroad include morphological methods, the gel electrophoresis of soluble seed proteins [4,5], direct analysis with real-time mass spectrometry [6], isoenzyme electrophoresis [7], liquid chromatography [8], and simple sequence repeat (SSR) analysis [9]. Morphological methods are highly demanding of experience for appraisers and the identification accuracy is easy subject to subjective factors.…”
Section: Introductionmentioning
confidence: 99%
“…For the enzyme alcohol dehydrogenase, polymorphism was verified between millet cultivars by Mendonça Neto et al (2013) when using this enzyme as a marker, although the same fact was observed by Vieira et al (2009), working with soybean and Menezes et al (2008) working with breeding lines and hybrids of maize. Using esterases as markers, by Vieira et al (2009), polymorphism was observed for soybean cultivar separation, as well as by Ferreira et al (2009) in Gladiolus and Mendonça Neto et al (2013) in millet crop. The same fact is reported by Vieira et al (2009) using the enzymes superoxide dismutase and peroxidase in studies with soybean cultivar polymorphisms observed for cultivar separation.…”
Section: Resultsmentioning
confidence: 61%
“…A total of 25 SSR primers described by Neto et al [ 9 ] shown in Table 1 were obtained from Inqaba Biotechnical Industries and were screened for polymorphism. This was done by randomly selecting 2 DNA samples from each of the regions (Zambezi, Karas, Kunene, Ohangwena, Okavango [East and West], Omusati, Oshana, Oshikoto, and Otjozondjupa) involved in the origin of all the accessions.…”
Section: Methodsmentioning
confidence: 99%